THE ACTIVITY OF GEL EXTRACT MAHKOTA DEWA FRUITS [(Phaleria macrocarpa (Scheff.) Boerl] THROUGH TYROSINASE ENZYME INHIBITOR - Aprilita Rina Yanti Eff; Erika Noviyanti; Ratih Dyah Pertiwi (FITOFARMAKA: Jurnal Ilmiah Farmasi, 2022)
Mahkota dewa fruit [(Phaleria macrocarpa (Scheff.) Boerl] contains benzophenone derivatives which have sun protection activity and flavonoid compounds which can act as tyrosinase inhibitors.  This study aimed to determine the tyrosinase inhibitor activity of 70% ethanol extract of Mahkota Dewa fruit and gel extract of Mahkota Dewa fruits with variations in concentrations of 1.25% (F1), 2.5% (F2), and 5% (F3). Assay of tyrosinase inhibitor activity against ethanol extract of Mahkota Dewa fruit and ethanol extract was done with various concentrations (31.25, 62.5, 125, 250, and 500 µg/ml), using a positive control of Kojic acid and L-DOPA as a substrate. Absorbance measurement was carried out using UV-vis microplate reader with a wavelength of 480 nm. The results showed that the ethanolic extract Mahkota Dewa had an IC50 value of 6668.06 µg/ml while kojic acid as a positive control possessed an IC50 value of 4.22 µg/ml. Gel preparation of the ethanol extract has inhibitor activity of the enzyme tyrosinase represent moderate values of the IC50each, i.e., F1 (1.25%) amounted to 285.03 µg/ml, F2 (2.5%) amounted to 373.25µg/ml, and F3 (5%) of 397.40 µg/ml. The tyrosinase inhibitor activity of the 70% ethanol extract of Mahkota Dewa fruit was lower with a relative potency of 5.167 x 10-3 times compared to that of kojic acid.